(−)-Pentazocine Induces Visceral Chemical Antinociception, but not Thermal, Mechanical, or Somatic Chemical Antinociception, in μ-Opioid Receptor Knockout Mice. Issue 1 (10th April 2011) - Ide, Soichiro; Minami, Masabumi; Uhl, George R; Satoh, Masamichi; Sora, Ichiro; Ikeda, Kazutaka
Background: (−)-Pentazocine has been hypothesized to induce analgesia via the κ-opioid (KOP) receptor, although the involvement of other opioid receptor subtypes in the effects of pentazocine remains unknown. In this study, we investigated the role of the μ-opioid (MOP) receptor in thermal, mechanical, and chemical antinociception induced by (−)-pentazocine using MOP receptor knockout (MOP-KO) mice. Results: (−)-Pentazocine-induced thermal antinociception, assessed by the hot-plate and tail-flick tests, was significantly reduced in heterozygous and abolished in homozygous MOP-KO mice compared with wildtype mice. The results obtained from the (−)-pentazocine-induced mechanical and somatic chemical antinociception experiments, which used the hind-paw pressure and formalin tests, were similar to the results obtained from the thermal antinociception experiments in these mice. However, (−)-pentazocine retained its ability to induce significant visceral chemical antinociception, assessed by the writhing test, in homozygous MOP-KO mice, an effect that was completely blocked by pretreatment with nor-binaltorphimine, a KOP receptor antagonist. In vitro binding and cyclic adenosine monophosphate assays showed that (−)-pentazocine possessed higher affinity for KOP and MOP receptors than for δ-opioid receptors. Conclusions: The present study demonstrated the abolition of the thermal, mechanical, and somatic chemical antinociceptive effects of (−)-pentazocine and retention of the visceral chemical antinociceptive effects of (−)-pentazocine in MOP-KO mice. These results suggest that the MOP receptor plays a pivotal role in thermal, mechanical, and somatic chemical antinociception induced by (−)-pentazocine, whereas the KOP receptor is involved in visceral chemical antinociception induced by (−)-pentazocine.